MANUSIA DAN PEMAKNAAN RUANG KOTA DALAM ANTOLOGI CERPEN SALOME DAN ORANG-ORANG BALIKPAPAN - Diyan Kurniawati (LOA: Jurnal Ketatabahasaan dan Kesusastraan, 2019)
This paper discusses the importance of city space for humans who live in it in the anthology of Salome and Orang-Orang Balikpapan. It uses sociological theory of literature and a theory of urban space. This study analyzes the position of humans in urban space and the importance of urban space for humans who live in it. Human position is displayed in various socio-economic classes. Therefore, relations between people in those various socio-economic classes will also be analyzed. It shows that the journey of human beings maintaining their existence in the city space brings together humans to other humans with various social, economic, and cultural backgrounds. Humans who migrate to urban spaces find attention and empathy from the others so that they can find new family and homes. The defense of their existence that is full of competition can cause other humans to develop empathy. In urban space, humans do not only buy and sale things, demand rights, and carry out obligations, but also can still show empathy to the others. Empathy demonstrated through attention to the development of others, especially children, is also a form of empathy that is very beneficial to the others. Short stories in Salome and Orang-Orang Balikpapan show humans in the urban space who maintain their social values in their intense competition maintaining their existence.